2016
DOI: 10.1002/2016gl069591
|View full text |Cite
|
Sign up to set email alerts
|

Ducted electromagnetic waves in the Martian ionosphere detected by the Mars Advanced Radar for Subsurface and Ionosphere Sounding radar

Abstract: In the data of the Mars Advanced Radar for Subsurface and Ionosphere Sounding on board the European Space Agency (ESA) mission Mars Express (MEX), a distinctive type of signals (called the “epsilon signature”), which is similar to that previously detected during radio sounding of the terrestrial F region ionosphere, is found. The signature is interpreted to originate from multiple reflections of electromagnetic waves propagating along sounder pulse‐created, crustal magnetic field‐aligned plasma bubbles (wavegu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(29 citation statements)
references
References 42 publications
4
25
0
Order By: Relevance
“…We indicate the extension of the interval for which a trace associated with the epsilon signature is visible by the red hatched region in Figure . Significantly, this leads to a clear connection between the epsilon signature reported by Zhang et al () and the peak density enhancements reported by Nielsen et al (), with the final reflection site of the T2 branch of the epsilon trace (the ionospheric footprint of the ducting field line) being colocated with the peak density enhancement.…”
Section: Observationssupporting
confidence: 66%
See 4 more Smart Citations
“…We indicate the extension of the interval for which a trace associated with the epsilon signature is visible by the red hatched region in Figure . Significantly, this leads to a clear connection between the epsilon signature reported by Zhang et al () and the peak density enhancements reported by Nielsen et al (), with the final reflection site of the T2 branch of the epsilon trace (the ionospheric footprint of the ducting field line) being colocated with the peak density enhancement.…”
Section: Observationssupporting
confidence: 66%
“…This is in addition to more complex signatures simultaneously detected resulting from ducted propagation of the sounder pulses along the field‐aligned irregularities, including a long‐distance duct that leads to reflections from the ionospheric peak, close to the region sampled by the nadir case from the first sounding. The most obvious signature of these ducted traces is the epsilon noted by Zhang et al (). We note the apparent lack of the isolated corresponding T1 trace in Figure d, which is expected at delays smaller than that of the nadir reflection on the basis of the properties of the T2 and T1+T2 traces (from which the expected T1 trace can be uniquely determined).…”
Section: Summary and Discussionmentioning
confidence: 88%
See 3 more Smart Citations